2018
DOI: 10.1159/000490986
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-142 Inhibits Proliferation and Promotes Apoptosis in Airway Smooth Muscle Cells During Airway Remodeling in Asthmatic Rats via the Inhibition of TGF-β -Dependent EGFR Signaling Pathway

Abstract: Background/Aims: Asthma is a heterogeneous disease characterized by chronic airway inflammation resulting from airway hyper-responsiveness to diverse stimuli. In this study, we investigated whether microRNA-142 (miR-142) expression affects proliferation and apoptosis in airway smooth muscle cells (ASMCs) during airway remodeling in asthmatic rats. Methods: Thirty six Wistar rats were randomly classified into a control group and an model group. miR-142 mimics and inhibitors were constructed, and ASMCs were tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, increased expression of several miRNAs inhibit ASMC proliferation or AHR via different pathways. Specifically, miR-19b-3p, miR23b-3p and miR-142-3p inhibit TGFβ-dependent ASMC proliferation (28)(29)(30). MiR-150-3p and miR-708-5p inhibit ASMC proliferation by downregulating BCYRN1 (31) and CD38 (33), respectively, while miR-384-5p reduces ASMC autophagy (32).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, increased expression of several miRNAs inhibit ASMC proliferation or AHR via different pathways. Specifically, miR-19b-3p, miR23b-3p and miR-142-3p inhibit TGFβ-dependent ASMC proliferation (28)(29)(30). MiR-150-3p and miR-708-5p inhibit ASMC proliferation by downregulating BCYRN1 (31) and CD38 (33), respectively, while miR-384-5p reduces ASMC autophagy (32).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, most of these miRNAs with the exception of miR-23b-3p, were increased in WT HDME mice in comparison to their PBS controls ( Figure 7B). Strikingly, in comparison to allergen-treated WT mice, Cd2 −/− HDMEtreated mice had higher expression of miRNAs that regulate polymeric mucin expression (24) (Figure 7C), inflammation (25)(26)(27) (Figure 7D), airway smooth muscle proliferation and AHR (28)(29)(30)(31)(32)(33) (Figure 7E). Recently it has been shown that Let-7 family of miRNAs can directly bind to the 3 ′ UTR of IL-13 mRNA and degrade it (34).…”
Section: Cd2 Regulates Various Mirna Expression In Asthmamentioning
confidence: 99%
“…The airway inflammation is orchestrated through multiple cell types, inflammatory mediators, and cytokines and involves a considerable number of conduction channels and regulatory networks. The manifestation of asthma is also brought about by the concerted effects of numerous pathways and large regulatory networks, such as the transforming growth factor β (TGF-β)/Smad signaling pathway [2], STAT3/NF-κB signaling pathway [3], IL-37 signaling pathway [4], Notch1-GATA3 signaling pathway [5], and many others [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is recognized as a critical contributor to pulmonary diseases including asthma, airway obstruction and pulmonary hypertension (13). Hypoxia stimulates airway inflammation and remodeling, and subsequently induces apoptosis in airway smooth muscle cells (ASMCs) during airway remodeling (4). There is emerging evidence for sex differences in the incidence and progression of lung diseases, and sex hormones play crucial roles in these pathological processes (5).…”
Section: Introductionmentioning
confidence: 99%